High-Speed and Wideband Frequency-Hopping Microwave Signal Generation via Switching the Bias Point of an Optical Modulator - Yang Chen (IEEE Photonics Journal)
A novel photonic approach to generate high-speed and wideband frequency-hopping microwave signal via switching the bias point of a dual-drive Mach-Zehnder modulator (DD-MZM) is proposed and experimentally demonstrated. The core component of the system is a DD-MZM. By switching the bias point of the DD-MZM between the quadrature transmission point and the minimum transmission point, frequency hopping between two frequencies can be realized with an ultra-high frequency-hopping speed and a very wide bandwidth. The proposed approach has a compact structure and good tunability. A proof-of-concept experiment is performed to verify the principle of the proposed technique. Tunable frequency-hopping microwave signals between two frequencies of 4 and 8 GHz, 9 and 18 GHz, or 12 and 24 GHz are generated with a frequency-hopping speed up to 1 GHz.